From Tsushima to Berlin and the Kurile Islands: Russian and Soviet naval power, 1905-1945 - Muraviev, Alexey (2025)
This chapter examines the changing fortunes of the Russian and Soviet navies from the defeat at Tsushima during the Russo-Japanese War to the end of the Great Patriotic War. During this period, Russia and the Soviet Union struggled, in the light of economic exigencies of the early inter-war period and inevitable focus on land power as a major war with neighbouring powers loomed on the horizon, to maintain the sort of naval forces that were expected of a major naval power. As a result, Soviet ambitions to become a major naval power and develop an 'ocean-going' fleet had to be put on hold by the late 1930s. Nonetheless, a certain level of naval power had become a non-negotiable imperative, without which Russia or the Soviet Union as sovereign nations would struggle to survive. The deployment of that naval power would be hampered by the geographically dispersed nature of the Russian and Soviet fleets and flotillas.